Common Variation in the CYP17A1 and IFIT1 Genes on Chromosome 10 Does Not Contribute to the Risk of Endometriosis - Zhao, Zhen Zhen (2008)
Endometriosis is a complex disease involving multiple susceptibility genes and environmental factors. Our previous studies on endometriosis identified a region of significant linkage on chromosome 10q. Two biological candidate genes (CYP17A1 and IFIT1) located on chromosome 10q, have previously been implicated in endometriosis and/or uterine function. We hypothesized that variation in CYP17A1 and/or IFIT1 could contribute to the risk of endometriosis and may account for some of the linkage signal on chromosome 10q. We genotyped 17 single nucleotide polymorphisms (SNPs) in the CYP17A1 and IFIT1 genes including SNP rs743572 previously associated with endometriosis in 768 endometriosis cases and 768 unrelated controls. We found no evidence for association between endometriosis and individual SNPs or SNP haplotypes in CYP17A1 and IFIT1. Common variation in these genes does not appear to be a major contributor to endometriosis susceptibility in our Australian sample.